2021
DOI: 10.1111/tbed.14395
|View full text |Cite
|
Sign up to set email alerts
|

Origin, genetic diversity, adaptive evolution and transmission dynamics of Getah virus

Abstract: As a member of the Alphavirus, Getah virus (GETV) was becoming more serious and posing a serious threat to animal safety and public health. However, the circulation, distribution and evolution of GETV is not well understood. Hence, we integrated a variety of bioinformatic methodologies, from genomic alterations to systematic analysis, phylogeography, selection, adaptive analysis, prediction of protein modification, structural biology and molecular dynamics simulations to understand the characteristics of GETV.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…With its wide geographic distribution and strong host adaptation as shown in one of our previous reports (Shi et al, 2021), GETV disease has been seriously jeopardizing the healthy development of the horse and pig industries in China and even the world, causing large losses to the livestock industry and posing an increasing potential threat to public health security. Up to now, GETV disease outbreaks in equine herds six times worldwide, among which, five times occurred in Japan and one time in India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With its wide geographic distribution and strong host adaptation as shown in one of our previous reports (Shi et al, 2021), GETV disease has been seriously jeopardizing the healthy development of the horse and pig industries in China and even the world, causing large losses to the livestock industry and posing an increasing potential threat to public health security. Up to now, GETV disease outbreaks in equine herds six times worldwide, among which, five times occurred in Japan and one time in India.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the structural protein encoded by the E gene not only constitutes the surface protrusion of the viral particle, but is the critical protein for the adsorption of GETV virus to target cells and the induction of anti-infection immunity in the host ( Voss et al, 2010 ). Based on the evolutionary analysis of the nucleotide sequence of the E2 gene or whole genome, GETV strains can be divided into four groups I–IV, and most of the strains prevalent in the world after 1964 belong to group III ( Li et al, 2017 ; Shi et al, 2021 ). As a re-emerging mosquito-borne disease, GETV disease is an increasingly prominent epidemic problem in China.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, GETV is an arbovirus with a broad spectrum of infection, and an RT-qPCR assay that can be applied to multiple species of swine, horses, bovines, sheep, and mosquitoes is of more practical application. One study performed multiple sequence alignment analysis and phylogenetic analysis of 45 whole-genome sequences, 71 E2, 47 E1, 61 Nsp1, and 57 Cap gene sequences of GETV from NCBI and found that the Nsp1 gene was the most stable and had the lowest mutation rate during the evolution of GETV transmission (Shi et al, 2021). In this study, specific primers were designed based on the conserved sequence of Nsp1 of GETV, and after optimization, the method was found to have excellent specificity, with a specific melting peak at 85.5 ± 0.5°C.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the identification of neutralizing antibodies against GETV from human serum showed that the antibody titers in fever patients were significantly higher than that of healthy individuals (Hu et al, 2012). As a widespread arbovirus, the epidemic scope and host numbers of GETV are expanding (Shi et al, 2021). What's more, in China, the transmission of GETV has been detected in 18 provinces so far (Lu et al, 2020), which has already caused serious economic losses to local farms.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, GETV infection has been reported in different mammalian orders other than their perceived reservoir host groups 25 . Therefore, although MXRA8 has been identified as a receptor for GETV, the rather limited expression profiles of MXRA8 in several tissues cannot explain the ability of GETV to infect large numbers of species and tissues 17 , 23 , 26 . It remained unknown whether receptors identified for other alphaviruses or some unknown receptors facilitate the cell entry of GETV 27 .…”
Section: Introductionmentioning
confidence: 99%